Intraocular Pressure Rise Linked to Silicone Oil in Retinal Surgery: A Review - Nicolai, Michele (Vision (Basel), 2020)
Silicone oil represents the main choice for intraocular tamponade in cases of complicated retinal detachment surgery. The intraocular pressure of an eye filled with silicone oil could increase, driven by a variety of different forces, according to several mechanisms. Two main conditions have been highlighted, depending on the onset: early hypertension or late glaucoma. The different types of silicone oils and their physico-chemical properties are varied and may play a role in the determination of intraocular pressure rise. The current body of literature allows for the illustration and categorization of the incidence and risk factors, as well as the pathogenesis and the management of the early postoperative hypertension subtended by an open- and closed-angle, along with the late onset silicone oil-induced glaucoma. Understanding the leading actors on the stage of ocular pressure elevation concurrently with silicone oil application for retinal surgery could help in guiding the timely and appropriate course of treatment.